Pengaruh Berbagai Dosis Pupuk Urea Terhadap Pertumbuhan Vegetatif Tanaman Jagung (Zea Mays L.) Di Berbagai Media Pasir - Nulhakim, Yudhi Lukman Nulhakim; Swardana, Ardli; Maesyaroh, Siti Syarah (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2025)
Corn (Zea mays L.) is a horticultural commodity with high economic value. This study aimed to examine the interaction and individual effects of various doses of urea fertilizer and different types of sand media on the vegetative growth of corn plants. The research was conducted in Kersamenak Village, Garut Regency, from June to August 2025. The method used was a 3x3 factorial Randomized Complete Block Design (RCBD) with three replications. The first factor was the dose of urea fertilizer (A), consisting of three levels: a1 = 100 kg,ha-1, a2 = 150 kg.ha-1, a3 = 200 kg.ha-1. The second factor was the type of sand media (M), consisting of three levels: m1 = Cilopang Sand, m2 = River Sand, and m3 = Leles Sand. The results showed that there was no significant interaction between the dose of urea fertilizer and the type of sand media on all parameters of corn plant vegetative growth. Individually, the application of urea fertilizer at a rate of 100 kg ha⁻¹ resulted in vegetative growth that had already reached its optimal level. Cilopang Sand tended to yield better leaf area growth compared to River Sand and Leles Sand.